KADYOS flour - Buendia, Rachel Irene; Kalaw, Angelica Beata; Pacolor, Anne Margaret; Sison, Kathryn
In response to the issue of making nutrition accessible to the Filipinos, the Philippine government has passed the Food Fortification Law 2000 (R.A. 8976) that requires food manufacturers to fortify the products with basic micronutrients. Compliance to this law entails additional manufacturing costs which are expected to be shouldered by the consumers. However, government agencies such as Department of Trade and Industry (DTI) and Department of Agriculture (DA) impose price control of basic needs and commodities. From this laws arises the business challenge faced by food manufacturers to maintain the nutritional value of food products adhering to the price control set by the government and staying competitive at the same time. As a solution, finding alternatives for existing raw materials that offers higher nutritional value at a lower cost will provide food manufacturers with business opportunities to stay at par with competitors while providing affordable and nutritious food to people. KADYOS takes pride in being the pioneer Pigeon Pea flour company in the Philippines producing premium, high-grade flour enriched with protein driven by the desire to bridge the gap between affordability and nutrition. Pigeon pea flour is a low-cost, locally available health enhancer that provides nutritionally adequate meals for the most vulnerable groups of the population by fortifying instant noodles, the most popular and low cost basic commodity in the country. Pigeon pea flo0ur has 28.55% protein, 5.24% fat, 2.5% crude fiber and 2.9% iron, which are relatively higher than wheat flour. The target market for Pigeon pea flour is the top instant noodle manufacturers: Monde Nissin, JG Summit Holdings Inc and Nissin Foods Holdings Co Ltd. The total demand of these companies captures 81.6% of the instant noodle market. Initial market to be served is 1% of Pigeon pea flour. The product banks on its competitive advantage of having raw material which is locally available unlike regular wheat flour. Pigeon pea flour will comprise 0.072% composition in weight of instant noodles. The projected annual demand for pigeon pea flour is 142.5024 metric ton based on the average forecasted demand for instant noodles in the next five years. Pigeon pea flour will be sold at PhP 750 per 25 kg. The total projected revenue for five years is equal to PhP 135,240,434.20. Using location planning with consideration to environmental condition required for growing pigeon peas, 30 hectare of pigeon pea plantation is located in a 58 hectare land at Brgy Baraka, Norzagaray, Bulacan supplying to the milling facility located at the same site. The plantation is expected to yield 750 kg and 2000 kg of seeds during the wet and dry season, respectively. The milling facility will be equipped with Mini Dal Mill with a capacity of 78 to 80 percent recovery rate with a yield of 109.2 to 112 kg of Pigeon pea flour per run. KADYOS flour aims to promote proper nutrition to Filipinos. Moreover, the production of flour will contribute in achieving the national goal of reducing wheat import by approximately 1%. Setting-up the company will increase the employment in the agricultural industry by 0.01%. Also, the by-products of the pigeon pea plant will be given to farmers, materials which can be used for other profitable products such as tea, hand-woven bags that will give more income to the farmers. The study proves the socio-economic profitability of the project.